Environment Challenges Of Present World: An Overview (Journal of Pharmaceutical Negative Results, 2022)
In today’s world the problem of environmental pollution is of great concern for all the countries despite their size, development or ideology. The environmental pollution is contributed by all the nations on this globe. Some countries have contributed it in earlier times and some countries are still not following the international treaties and convention and contributing the pollution which resulted to the global warming and many other effects. Though in developed states the governments has started taking the remedial measures inensuring the minimum pollution, but still much more is needed and required to minimize the pollution. The situation in the developing nations and the poor nations is alarming, as more efforts are needed to overcome the environment pollution. It is the basic right of every person to live in a healthy environment and for that it is prime requirement that international bodies must check the proper implementation of the Laws relating to Environmental Pollution Worldwide. Here the role of the developed states is also equally important, as they have to take care the needs of the poor and developing nations. All these issues with the important suggestions are discussed in this paper.